Implementasi ASEAN Tourism Strategic Plan (ATSP) Dalam Pengembangan Pariwisata Bali - Byomantara, Dewa Gede Ngurah; Sucipta, I Gusti Ngurah Oka Dwi; Octaviani, Iva (HeadWay Research & Developemnt, 2024)
Tourism plays a very important role in Bali's economy, being the main sector that drives economic growth and provides many jobs. As an international tourist destination, Bali attracts millions of tourists every year, making a significant contribution to regional GDP. High dependence on tourism makes Bali's economy vulnerable to fluctuations in the number of tourists. A decline in tourists, such as during a global crisis or pandemic, has a major impact on the economy, underscoring the importance of economic diversification to reduce over-reliance on the sector. The purpose of writing this article is to investigate and analyze how Bali, as a major tourist destination in ASEAN, implements the strategies listed in the ATSP to strengthen and develop its tourism sector. The method used is a literature study carried out by collecting and analyzing various sources of information related to the implementation of the ASEAN Tourism Strategic Plan (ATSP) in the development of Bali tourism. The results of this research are that the application of the concept of sustainable tourism and the implementation of the ASEAN Tourism Strategic Plan (ATSP) in Bali have increased the growth of the tourism sector with a focus on preserving culture and the environment, as well as empowering local communities. Stakeholder coordination and funding challenges can be overcome with a holistic approach, while opportunities for further development include diversification of tourism products and improving the quality of human resources